A Recently Discovered Bell: Artifact, Metaphor, Secrets, and Identity in an Italian American Family. (August 2018) - Reale, Michelle
Secrets in families are often toxic, leading to a sense of bewilderment at one's own identity. Within the context of family origins, the discovery of seemingly simple and ordinary artifacts, far from being revelatory, can further obscure meaning and understanding of the person to whom it belonged. The effect of secrets can reverberate for generations affecting who we are, where we come from, and who we have the potential to be.